Migration Reform in the United States: Perspectives of Change and Continuity - Méndez Coto, Marco Vinicio (2017)
The article proposes an analysis of migration from the perspective of security (as it has been addressed by countries such as the United States mainly receiving international immigrants), and within the terrorism and the prevention context in which the international community is. The complexity of the migration issue has an impact on changes in the United States internal policy and generates transformations in the immigration system. These transformations appear in certain aspects like those contemplated in the Border Security, Economic Opportunity, and Immigration Modernization Bill (S.744) which was promoted by the President Obama. This section explains the process of change in the American political and electoral panorama since 2008 elections, the Latin America role in the foreign policy of Obama’s administration, the growing electoral power of Hispanic descendant population in the United States, the current situation of the immigrant population in an irregular administrative situation, and the current context of the bill within the American political system.